Bench-scale steam reforming of methane for hydrogen production - Park, Hae Gu; Han, Sang Young; Jun, Ki Won; Woo, Yesol; Park, Myung June; Kim, Seok Ki (Catalysts, 2019)
The effects of reaction parameters, including reaction temperature and space velocity, on hydrogen production via steam reforming of methane (SRM) were investigated using lab-and bench-scale reactors to identify critical factors for the design of large-scale processes. Based on thermodynamic and kinetic data obtained using the lab-scale reactor, a series of SRM reactions were performed using a pelletized catalyst in the bench-scale reactor with a hydrogen production capacity of 10 L/min. Various temperature profiles were tested for the bench-scale reactor, which was surrounded by three successive cylindrical furnaces to simulate the actual SRM conditions. The temperature at the reactor bottom was crucial for determining the methane conversion and hydrogen production rates when a sufficiently high reaction temperature was maintained (>800◦C) to reach thermodynamic equilibrium at the gas-hourly space velocity of 2.0 L CH4/(h·gcat). However, if the temperature of one or more of the furnaces decreased below 700◦C, the reaction was not equilibrated at the given space velocity. The effectiveness factor (0.143) of the pelletized catalyst was calculated based on the deviation of methane conversion between the lab-and bench-scale reactions at various space velocities. Finally, an idling procedure was proposed so that catalytic activity was not affected by discontinuous operation.
Keywords: Bench scale; Effectiveness factor; Hydrogen production; Methane steam reforming